Tillage effects on phosphorus fractions of freshwater wetlands - QIN Sheng-jin; LIU Jing-shuang; WANG Guo-ping; ZHOU Wang-ming (浙江大学学报. 农业与生命科学版, 2008)
In order to discuss the influence of reclamation on wetland soil P, a modified Hedley P fractionation method was employed to compare the variations of P fractions between wetland soil, farmland and abandoned farmland in Sanjiang Plain, China. It can be found that the content of total inorganic P (TPi) increased 319.67 mg·kg-1 after 3-year tillage (G3), and the labile and secondary available Pi increased in a wider range (P<0.05), while the total organic P (TPo) decreased 313.28 mg·kg-1. The content of Pi decreased with tillage time. For 8-year tillage (G8) soil, the contents of Resin-P, NaHCO3-Pi and NaOH-Pi were only 28.18%, 42.87% and 45.90% respectively, as much as those for G3. The content of Po increased with tillage time, but only NaOH-Po presented a relative larger increment (P>0.05). The status of soil P in abandoned farmland tended to approach that of wetland. The content of all the P fractions increased after abandoned, except Conc. HCl extracted fraction, however the Po increased in a comparatively lower speed. The content of secondary available P varied in the widest range, which is the main source and sink of P in the wetland of Sanjiang Plain.